Testing the J-Curve Hypothesis: A Case of Nepal - Chaulagai, Mahesh Kumar (NRB Economic Review, 2015)
This paper attempts to explore the J-curve phenomenon in the case of Nepalese foreign trade sector in order to examine whether devaluation2 of Nepalese currency can be taken as a policy tool for improving Nepalese trade imbalance with the rest of the world economies. Johansen's cointegration test, vector autoregression (VAR) model, impulse response function as well as autoregressive distributed lag (ARDL) bounds testing cointegration approach has been employed in order to see the relationships between the nominal effective exchange rate index (NEER) and trade balance (TB) as well as the real effective exchange rate index (REER) and trade balance (TB) of Nepal. The study found no evidence of "J-curve" in the case of Nepalese trade. On the contrary to the "J-curve" phenomenon as explained by the classical text books, the findings of the study suggest that depreciation of Nepalese exchange rate rather produces a flatter "L-curve" phenomenon indicating that there is no room for improving Nepalese trade imbalance through a currency devaluation process.